Ascorbic acid determination using a carbon paste electrode modified with iron(III) ions adsorbed on humic acid - da Silva, Lucinei Stechmann; Oliveira, Tiago Nieswald; Ballin, Marco Aurélio; Peixoto, Carlos Roberto de Menezes (Eclética Química, 2006)
An amperometric sensor was constructed, by using humic acids to immobilize Fe 3+ ions on a carbon paste electrode (CPE-HA-Fe), and used for ascorbic acid (H 2 A) determination. The cyclic voltammogram of the electrode showed electrochemical response due to the Fe 3+ /Fe 2+ couple at E 1/2 =+0.78 V vs SCE, using 0.5 mol L -1 KCl and 0.2 mol L -1 acetate/0.020 mol L -1 phosphate buffer, at pH = 5.4, as supporting electrolyte. When H 2 A is added to the electrolyte solution it is observed an oxidation process. The oxidation current, obtained by chronoamperommetry at +0.87 V vs SCE, is proportional to the concentration, represented by the equation I(μA) = 7.6286 [H 2 A] (mmol L -1 ) + 1.9583, r = 0.9996, for concentrations between 0.0 and 1.4 mmol L -1 . The electrode showed high stability and was used for H 2 A determination in a natural orange juice.